Efektivitas Implementasi Sistem Informasi Manajemen BAZNAS dalam Meningkatan Mutu Pengelolaan Zakat, Infaq dan Sedekah - Mahfiza Mahfiza; Arsyad Paweroy; Hamsil Hamdi (Al-Buhuts, 2023)
This study aims to examine the application of BAZNAS management information systems in improving the quality of zakat, infaq and donate management at BAZNAS. The method used in this research is descriptive qualitative method. data collection is done by interviews, observation, and documentation. Data analysis was done by data reduction, presented and given a conclusion. The results of the study prove that the implementation of the BAZNAS management information system can improve the quality, performance and professionalism of the management of zakat, infaq and alms to be more effective, starting from the collection, distribution and empowerment of Zakat, Infak and Alms, so as to increase the interest of muzakki to channel their zakat through institutions BAZNAS zakat manager. Factors supporting the implementation of simba at BAZNAS make it easier for amil in collecting and allocating Zakat, Infak and Alms funds. While the inhibiting factor is the lack of understanding of Amil regarding the operation of the SIMBA application. The application of simba was realized well after the amils attended special training related to the SIMBA application